Before Iglulik: Inuit Memory and Recent-Historic Archaeology at Avvajja, Nunavut - Desjardins, Sean; LeBlanc, Sylvie (Études Inuit Studies, 2022)
Before Iglulik is an archaeological and oral-historical project undertaken to record and document Inuit settlements around Iglulik (Igloolik) during the period preceding the establishment of modern hamlets in the Canadian Arctic in the mid-20th century. The archaeological component of the research consisted of recording and mapping features at Avvajja, an early 20th-century campsite located approximately six kilometers northwest of Iglulik, while the oral history component involved the facilitation of Inuit engagement with these cultural remains. A series of interviews and site visits were held with former residents of Avvajja (Avvajjamiut). To promote cross-generational knowledge transmission, a reunion event at the site was coordinated by the authors for Avvajjamiut and their loved ones. Attendees shared a feast at the site and toured their ancestors’ dwellings, where many stories were shared.